Components of the metabolic syndrome and depressive symptoms in community-dwelling older people: the Bambuí Cohort Aging Study - Ruas, Luiz Gustavo (Braz J Psychiatry, 2016)
OBJECTIVE: To investigate the moderating effect of an increasing number of clustered metabolic syndrome (MetS) components on the association between MetS and depressive symptoms in a population-based cohort of older adults in Brazil. METHODS: This analysis used data from the Bambuí Cohort Aging Study. Participants in this cross-sectional study comprised 1,469 community-dwelling older people aged ≥ 60 years. Analyses were performed to assess both the association between depressive symptoms and each individual MetS component and the association between depressive symptoms and clustering of an increasing number of MetS components. RESULTS: High triglyceride level was the individual component that showed the strongest association with depressive symptoms (odds ratio [OR]: 1.47; 95% confidence intervals [95%CI] 1.19-1.81; p < 0.0001). Only the presence of three MetS components was associated with depressive symptoms (OR = 1.53; 95%CI 1.05-2.23; p = 0.025). No graded association was detected between increasing number of clustered MetS components and depressive symptoms. CONCLUSIONS: Increasing the number of MetS components did not impact the association with depressive symptoms. The association between high triglyceride level and depressive symptoms highlights the relevance of lipid metabolism abnormalities for the emergence of depressive symptoms in older adults.